VERBAL PARTICIPATION IN THE DICTIONARY OF AL- MISBAH IN THE COMBINATION OF ALAFA’AL AND SEHAH BY IMAM AL-QURTUBI) D.671 AH(SEMANTIC STUDY) - Shaima Mohammed Sabry, Dr. Ammar sabaar karim (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The Arabic language was distinguished by a number of characteristics, which made it a rich language with renewed meanings. Among those characteristics is participation , and to know this feature and how it contributed to enriching the language, the research deals with this phenomenon, and because it is one of the linguistic phenomena that can only be monitored through a dictionary that includes language terms and their various meanings. I chose this dictionary as a field of study, as it has not been investigated yet and has not been covered in the study before. In that, we referred to three approved written copies, and the books from which AL-Qurtubi collected his material. So I extracted the text as the author wanted it, and dealt with it in the study of this phenomenon.